Resilience as a protective factor to academic Burnout in adolescents during COVID-19 - Ángel Alberto Puig-Lagunes; León Jesús German-Ponciano; Guerson Yael Varela-Castillo; Fabiola Ortiz-Cruz; Gilberto Uriel Rosas-Sánchez; Rodrigo Ramírez-Rodríguez (Journal of Affective Disorders Reports)
Background: COVID-19 pandemic increased academic concerns and risk for development of academic burnout syndrome (ABS) among adolescents. In Mexico, little research has been conducted on the impact of resilience in adolescents as a potential coping strategy against ABS. Therefore, this study aimed to examine the link between resilience and ABS symptoms in Mexican high school adolescents during the COVID- 19 pandemic. Method: An analytical and observational cross-sectional study was conducted with 2,194 adolescents from nine public high schools in Veracruz. Resilience and ABS were assessed between May-June 2021 by Google form, using the Mexican Resilience Scale and the Maslach Burnout Inventory - Student Survey. Using resilience domains, we conducted a binomial logistic regression model to predict the protective or risk factors for burnout syndrome. Results: A total of 9.73 % of adolescents exhibited symptoms of ABS. Female gender was found to be significantly associated with ABS. Furthermore, lack of value in domains such as strength and self-confidence (OR = 2.14, 95 % CI: 0.59–1.57), family support (OR = 1.89, 95 % CI: 1.47–2.44), and structure (OR = 1.62, 95 % CI: 1.22–2.16) were identified as risk factors for the development of burnout syndrome. In contrast, increase of value in social support (OR = 0.59, 95 % CI: 1.22–2.16) emerged as a protective factor. Conclusions: Resilience served as a crucial protective factor against ABS in high school adolescents highlighting the need for interventions aimed at promoting their emotional well-being, particularly among females.